Transmission characteristics of Tomato chlorosis virus (ToCV) by Bemisia tabaci MED and its effects on host preference of vector whitefly - Ke-ke WEI; Jie LI; Tian-bo DING; Tong-xian LIU; Dong CHU (Journal of Integrative Agriculture, 2019)
The epidemiology of Tomato chlorosis virus (ToCV) in China is closely associated with its vector whitefly, Bemisia tabaci (Gennadius) MED. However, the transmission characteristics of ToCV by B. tabaci MED remain poorly understood. In this study, we analyzed: 1) the horizontal and vertical transmission of ToCV by B. tabaci MED whiteflies; 2) the acquisition of ToCV by male and female B. tabaci MED whiteflies after different feeding durations; 3) the transmission efficacy of viruliferous male and female B. tabaci MED whiteflies after different inoculation access periods (IAPs); 4) the retention of ToCV by viruliferous male and female B. tabaci MED whiteflies after a 48 h acquisition access period (AAP); and 5) the effects of ToCV on host choice of healthy or ToCV-infected tomato plant of viruliferous and non-viruliferous B. tabaci MED at different time points. Our results showed that: 1) viruliferous males could not transfer ToCV to non-viruliferous females, and vice versa, viruliferous females could not pass on ToCV to non-viruliferous males. ToCV could not be detected in the F1 generation adults; 2) ToCV could be detected within 4.0% of females or males after a 20 min AAP; 3) ToCV could be detected in 33.3% of tomato plants inoculated by 10 viruliferous males or females with IAPs of 20 or 30 min; 4) the maximum retention time in females was 7 and 5 days in males; and 5) non-viruliferous B. tabaci MED did not show a preference for ToCV-infected tomato plants or healthy tomato plants. However, viruliferous B. tabaci MED whiteflies did prefer to settle on healthy tomato plants over ToCV-infected tomato plants. These findings will be helpful to better understand the epidemiology of the recently emerged plant virus, ToCV, in tomato fields in China.